Associations of Dietary Vitamin C and E Intake With Depression. A Meta-Analysis of Observational Studies - Ding, Jun; Zhang, Yi (Frontiers in Nutrition, 2022)
Objective: The associations of dietary vitamin C and E intake with depression remains conflicting. This meta-analysis of observational study was therefore employed to clarify the issue further. Methods: An extensive literature review (PubMed, Web of Science and Embase) was performed in January 2022 to identify the observational studies on the associations of dietary vitamin C and E intake with depression. The pooled relative risk (RR) of depression for the highest versus lowest dietary vitamin C and E intake category, and the weighted mean difference (WMD) of dietary vitamin C and E intake for depression versus control subjects, were calculated. Results: A total of 25 observational studies (91966 participants) were included in this meta-analysis. The overall multi-variable adjusted RR demonstrated that dietary vitamin C intake was inversely associated with depression (RR=0.72, 95%CI: 0.57 to 0.91; P=0.005). In addition, the combined WMD showed that the dietary vitamin C intake in depression was lower than that in control subjects (WMD=-11.58, 95%CI: -14.88 to -8.29; P<0.001). Similarly, the overall multi-variable adjusted RR demonstrated that dietary vitamin E intake was negatively associated with depression (RR=0.84, 95%CI: 0.72 to 0.98; P=0.02). Moreover, the combined WMD showed that the dietary vitamin E intake in depression was also lower than that in control subjects (WMD=-0.71, 95%CI: -1.07 to -0.34; P<0.001). Conclusions: The results of this meta-analysis suggest that both dietary vitamin C and E intake is inversely associated with depression. However, due to the limited evidence, more well-designed prospective cohort studies are still needed.